Simulation using discriminant analysis the course of pyoderma in men and women of western region of Ukraine depending on the characteristics of constitutional parameters of body = Моделювання за допомогою дискримінантного аналізу перебігу піодермій у чоловіків і жінок західного регіону України в залежності від особливостей конституціональних параметрів тіла - Yu. Ya. Kryvko; I. V. Gunas; R. S. Vastyanov; I. O. Chaplyk-Chyzho (Kazimierz Wielki University, 2016)
Kryvko Yu. Ya., Gunas I. V., Vastyanov R. S., Chaplyk-Chyzho I. O. Simulation using discriminant analysis the course of pyoderma in men and women of western region of Ukraine depending on the characteristics of constitutional parameters of body = Моделювання за допомогою дискримінантного аналізу перебігу піодермій у чоловіків і жінок західного регіону України в залежності від особливостей конституціональних параметрів тіла. Journal of Education, Health and Sport. 2016;6(6):599-605. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56742 http://ojs.ukw.edu.pl/index.php/johs/article/view/3648       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016.       UDC 612.66/.661:616.5-002.3   SIMULATION USING DISCRIMINANT ANALYSIS THE COURSE OF PYODERMA IN MEN AND WOMEN OF WESTERN REGION OF UKRAINE DEPENDING ON THE CHARACTERISTICS OF CONSTITUTIONAL PARAMETERS OF BODY   Yu. Ya. Kryvko, I. V. Gunas*, R. S. Vastyanov**, I. O. Chaplyk-Chyzho Lviv National Medical University named after Danylo Halytsky, *International Academy of Integrative Anthropology, **Odessa National Medical University   Summary The article describes and analyzed built, using discriminant analysis models of possible course of pyoderma in men and women of western regionsUkraine, depending on the characteristics of the structure and size of the body. Prove the possibility to predict the course of pyoderma based on the constitutional parameters of the body in both men (73.3% correct models of cases with different forms of dermatosis, statistics Wilks' Lambda = 0.416, p <0.001) and in women (68.8% correct models of cases with different forms of dermatosis; statistics Wilks' Lambda = 0,386; р<0,001), which is confirmed by practical test of their work on another sample of male patients (from 66.7% to 75.0% of cases with different forms of dermatosis) and women (from 50.0% to 80.0% of cases with different forms of dermatosis) of similar age and residence.   Key words: discriminant model, peculiarities of pyoderma, men and women in Western Ukraine.   МОДЕЛЮВАННЯ ЗА ДОПОМОГОЮ ДИСКРИМІНАНТНОГО АНАЛІЗУ ПЕРЕБІГУ ПІОДЕРМІЙ У ЧОЛОВІКІВ І ЖІНОК ЗАХІДНОГО РЕГІОНУ УКРАЇНИ В ЗАЛЕЖНОСТІ ВІД ОСОБЛИВОСТЕЙ КОНСТИТУЦІОНАЛЬНИХ ПАРАМЕТРІВ ТІЛА   Ю. Я. Кривко, І. В. Гунас*, Р. С., Вастьянов**, І. О. Чаплик-Чижо   Львівський національний медичний університет імені Данила Галицького, *Міжнародна академія інтегративної антропології, **Одеський національний медичний університет   Резюме В статті описано та проведено аналіз побудованих, за допомогою дискримінантного аналізу, моделей можливого перебігу піодермій у чоловіків і жінок західних регіонів України в залежності від особливостей будови та розмірів тіла. Доведено можливість прогнозувати перебіг піодермій на основі конституціональних параметрів тіла як у чоловіків (коректність моделей 73,3 % випадків при різних формах дерматозу; статистика Уілкса лямбда = 0,416; р<0,001), так і у жінок (коректність моделей 68,8 % випадків при різних формах дерматозу; статистика Уілкса лямбда = 0,386; р<0,001), що підтверджується практичною перевіркою їх роботи на іншій вибірці хворих чоловіків (від 66,7 % до 75,0 % випадків при різних формах дерматозу) і жінок (від 50,0 % до 80,0 % випадків при різних формах дерматозу) аналогічного віку та місця проживання.   Ключові слова: дискримінантні моделі, особливості перебігу піодермій, чоловіки та жінки західного регіону України.     Резюме МОДЕЛИРОВАНИЕ С ПОМОЩЬЮ ДИСКРИМИНАНТНОГО АНАЛИЗА ТЕЧЕНИЯ ПИОДЕРМИЙ У МУЖЧИН И ЖЕНЩИН ЗАПАДНОГО РЕГИОНА УКРАИНЫ В ЗАВИСИМОСТИ ОТ ОСОБЕННОСТЕЙ КОНСТИТУЦИОНАЛЬНЫХ ПАРАМЕТРОВ ТЕЛА. В статье описано и проведено анализ построенных с помощью дискриминантного анализа моделей возможного течения пиодермий у мужчин и женщин западных регионов Украины в зависимости от особенностей строения и размеров тела. Доказано возможность прогнозировать течение пиодермий на основе конституциональных параметров тела как у мужчин (корректность моделей 73,3 % случаев при разных формах дерматоза; статистика Уилкса лямбда = 0,416; р<0,001), так и у женщин (корректность моделей 68,8 % случаев при разных формах дерматоза; статистика Уилкса лямбда = 0,386; р<0,001), что подтверждается практической проверкой их работы на другой выборке больных мужчин (от 66,7 % до 75,0 % случаев при разных формах дерматоза) и женщин (от 50,0 % до 80,0 % случаев при разных формах дерматоза) аналогичного возраста и места проживания.   Ключовые слова: дискриминантные модели, особенности течения пиодермий, мужчины и женщины западных регионов Украины.